Efektivitas Penerapan Sanksi Pidana terhadap Pelanggaran Parkir di Badan Jalan (Suatu Penelitian di Dinas Perhubungan Kota Banda Aceh) - Muhammad Al Kausar; Muhammad Iqbal; Wiratmadinata Wiratmadinata; Jummaidi Saputra; Anhar Nasution (Prodi Ilmu Hukum, Universitas Teuku Umar, 2023)
Article 106 paragraph (40 letter e of Law Number 22 of 2009 Concerning Road Traffic and Transportation explains that everyone driving a vehicle on a road must comply with the provisions for stopping and parking. Furthermore, Article 287 states that everyone driving a motorized vehicle on a road that violating the rules of order or prohibition stated by traffic signs as referred to in Article 106 paragraph (4) letter b shall be punished by imprisonment for a maximum of 2 (two) months or a fine of a maximum of Rp. 500,000.00 (Five hundred thousand rupiahs). The criminal act was seriously threatened, but in practice the application of the crime has not been carried out, in fact there are still many violations. The purpose of this study is to explain the legal basis for applying criminal sanctions for parking violations on the street, the factors that cause parking violations on the road and explain the efforts made in dealing with parking violations on the road. In writing this thesis the writer uses empirical juridical methods. The empirical juridical method is legal research regarding the enactment or provisions for the implementation of normative law in action on certain legal events that occur in society. Library research was conducted to obtain secondary data, while field research was conducted to obtain primary data through interviews with respondents and informants. The results of the study show that although the rules in the law on traffic and road transportation have been implemented, they are not yet effective, namely because there are still some people who are negligent with traffic signs and the limited availability of parking space in the city of Banda Aceh. Obstacles faced in applying these criminal sanctions are socialization that has not been maximized, the unavailability of sufficient parking lots and the low awareness of violators to comply with the rules. Factors causing parking violations on the road are habitual factors, infrastructure factors, vehicle volume factors, natural conditions factors. Efforts made to deal with violations of parking on the road are the provision of parking lots, outreach, warnings, enforcement, imposition of sanctions. It is suggested to the law enforcement officers of the Banda Aceh City Transportation Service to be able to provide strict sanctions, socialize traffic signs and control overall vehicle drivers, especially four-wheeled vehicles so that these rules are actually realized.